Cascade Reaction between Methyl 3-Dehydroshikimate, Arylamines, and 2-Chloroalkyl Esters under Microwave Conditions: A Practical and Biomass-Based Synthesis of N-Aryl-1,4-benzoxazin-3-ones - Zhang, Ensheng; Xu, Tianlong; Wei, Wen; Huang, Tongkun; Yuan, Mu; Zeng, Wei; Zou, Yong (Synthesis, 2014)
A biomass-based, metal- and ligand-free assembly of N-aryl-1,4-benzoxazin-3-ones from methyl 3-dehydroshikimate (3-MHDS), involving aliphatic to aromatic transformation followed by C–O and C–N forming reactions, is presented. A variety of N-aryl-1,4-benzoxazin-3-ones were efficiently synthesized in a one-pot consecutive manner under microwave conditions.
Keywords: methyl 3-dehydroshikimate; N-aryl-1,4-benzoxazin-3-ones; metal-free; cascade reaction; cyclization